Hormonal response to lipid and carbohydrate meals during the acute postprandial period - Alleman Rick J; Bloomer Richard J (Taylor & Francis Group, 2011)
Abstract Background Optimizing the hormonal environment during the postprandial period in favor of increased anabolism is of interest to many active individuals. Data are conflicting regarding the acute hormonal response to high fat and high carbohydrate feedings. Moreover, to our knowledge, no studies have compared the acute hormonal response to ingestion of lipid and carbohydrate meals of different size. Methods We compared the hormonal response to lipid and carbohydrate meals of different caloric content during the acute postprandial period. Nine healthy men (22 ± 2 years) consumed in a random order, cross-over design one of four meals/beverages during the morning hours in a rested and fasted state: dextrose at 75 g (300 kcals), dextrose at 150 g (600 kcals), lipid at 33 g (300 kcals), lipid at 66 g (600 kcals). Blood samples were collected Pre meal, and at 0.5 hr, 1 hr, 2 hr, and 3 hr post meal. Samples were assayed for testosterone, cortisol, and insulin using ELISA techniques. Area under the curve (AUC) was calculated for each variable, and a 4 × 5 ANOVA was used to further analyze data. Results A meal × time effect (p = 0.0003) was noted for insulin, with values highest for the dextrose meals at the 0.5 hr and 1 hr times, and relatively unaffected by the lipid meals. No interaction (p = 0.98) or meal (p = 0.39) effect was noted for testosterone, nor was an interaction (p = 0.99) or meal (p = 0.65) effect noted for cortisol. However, a time effect was noted for both testosterone (p = 0.04) and cortisol (p < 0.0001), with values decreasing during the postprandial period. An AUC effect was noted for insulin (p = 0.001), with values higher for the dextrose meals compared to the lipid meals (p < 0.05). No AUC effect was noted for testosterone (p = 0.85) or cortisol (p = 0.84). Conclusions These data indicate that 1) little difference is noted in serum testosterone or cortisol during the acute postprandial period when healthy men consume lipid and dextrose meals of different size; 2) Both testosterone and cortisol experience a drop during the acute postprandial period, which is similar to what is expected based on the normal diurnal variation--feeding with lipid or dextrose meals does not appear to alter this pattern; 3) dextrose meals of either 75 g or 150 g result in a significant increase in serum insulin, in particular at 0.5 hr and 1 hr post-ingestion; 4) lipid meals have little impact on serum insulin.